Struggle for Resources Water: Analysis Conflict and Politics of Spatial Planning - Lukman Hakim, Agus; M Kolopaking, Lala; Siregar, Hermanto; Kumala Putri, Eka Intan (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2017)
ABSTRACTImplementation of local government regulation on spatial planning in Pandeglang Regency faced many obstacles, such as conflict between residents and companies in the Village Cadasari, Pandeglang Regency. The purpose of this research is to identify struggle for resources and the involved parties as well as to analyze the failure factors of Pandeglang Local Government to implement the spatial policy. This study used a qualitative descriptive approach. The results of the study illustrated that there were conflicts between company’s pros and cons. company’ cons, led by kiyai (Islamic priest), were citizens and students whom negatively affected by the establishment of company that caused difficulties of water resources access for daily needs and irrigation. On the other hand, company’s pros were Cadasari and Sukaindah village apparatus and some residents who wished to get benefit from increased employment opportunities supported by the Government of Pandeglang. The conflict was caused by the Local Government of Pandeglang who didn’t act as regulator and conflict resolution mediator but defended the existence of company while ignored the spatial planning. This proved that spatial policy is not only about technical aspect but also political one.Keywords: Politic of spatial planning, conflict, local government, resourcesABSTRAKImplementasi Perda RTRW Kabupaten Pandeglang menghadapi banyak kendala, diantaranya konflik antara warga dengan perusahaan di Desa Cadasari Kabupaten Pandeglang. Tujuan penelitian ini adalah untuk mengidentifikasi konflik perebutan sumber daya air, pihak terkait dan alternatif solusinya serta menganalisis faktor penyebab kegagalan Pemda Pandeglang dalam melaksanakan kebijakan tata ruang. Penelitian ini dianalisis dengan pendekatan deskriptif kualitatif. Hasil penelitian menggambarkan konflik terjadi antara pihak yang setuju pendirian perusahaan dan yang kontra. Pihak yang kontra perusahaan adalah warga, santri, dan kiyai yang mendapat efek negatif pendirian perusahaan berupa kesulitan akses sumber daya air dan irigasi sawah. Pihak yang pro perusahaan adalah aparatur Desa Cadasari, sebagian warga yang berharap memperoleh manfaat peluang kerja serta Pemda Pandeglang. Konflik tersebut disebabkan Pemda Pandeglang tidak menjadi regulator dan mediator penyelesaian konflik tapi cenderung memihak perusahaan dengan mengabaikan RTRW. Hal tersebut menunjukkan kebijakan tata ruang adalah political aspect bukan technical aspect.Kata kunci: Politik tata ruang, konflik, Pemda Pandeglang, sumberdaya